Effectiveness of a video-assisted teaching program on menstrual cup usage among women (18–45 years age group) in selected colleges of Patna - K. Lakshmi Prasanna; Sangam Jha; Naveen Kumar Sharma; Jyoti Rani (Journal of Family Medicine and Primary Care)
Introduction: Menstrual cups are a sustainable alternative to traditional menstrual products, yet their usage remains low in many regions. In India, only 0.3% of women use menstrual cups, representing a lack of knowledge and a negative attitude towards the use of menstrual cups. This study aimed to promote menstrual cup usage and develop the right attitude among women (18–45 years old) in selected colleges in Patna. Material and Methods: One group pre-test-post-test quasi-experimental study was conducted in selected colleges in Patna with a nonrandomized convenient sampling technique employed to select 100 participants. The intervention consisted of a 30-minute video session on menstrual cup usage, and a structured questionnaire administered pre- and post-intervention to assess knowledge and attitudes. Results: Post-intervention analysis showed a significant increase in knowledge and positive attitudes towards menstrual cup usage. The video-assisted teaching program was found effective in enhancing knowledge regarding menstrual cup usage, as evidenced by the mean knowledge score, which improved from 7.25 + 1.89 to 8.40 + 1.43, as well as the attitude mean score, which improved from 32.14 + 8.50 to 33.91 + 7.88. Conclusion: The video-assisted teaching program effectively enhanced knowledge and positively influenced attitudes toward menstrual cup usage among women in the targeted age group. This suggests that similar educational interventions could be beneficial in promoting sustainable menstrual hygiene practices. Many participants suggested that if it is added through government schemes, it will be more valuable in promoting the adoption of menstrual cups among women.